1983
DOI: 10.1139/v83-371
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of N-[[6-methoxy-5-(trifluoromethyl)thio-1-naphthalenyl]thioxomethyl]-N-methylglycine, C16H14F3NO3S2

Abstract: The crystals of C16H14F3NO3S2 belong to the monoclinic space group P21/c with a = 11.577(1), b = 12.404(1), c = 12.366(1) Å, β = 90.01(1)°, and Z = 4. The structure was solved by MULTAN 78. The parameters were refined by block-diagonal least-squares to a final R of 0.047 for 2679 observed reflections. Of particular interest is an intramolecular attractive interaction between the sulfur and oxygen atoms with an [Formula: see text] distance of 2.879(2) Å, in which oxygen appears to act as an electrophile. Interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In the myotropic assay, the analog retained in the ground state 80% of the maximal response obtained with the parent kinin pentapeptide (Table 1). This slight activity loss may result from the larger size of the sulfur atom [42,43], the longer carbon-sulfur bond length [44,45], and the different electron distribution of thioxopeptide bond ψ[CS-N] [46]. In the photostationary state, a fourfold enhanced myotropic activity was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the myotropic assay, the analog retained in the ground state 80% of the maximal response obtained with the parent kinin pentapeptide (Table 1). This slight activity loss may result from the larger size of the sulfur atom [42,43], the longer carbon-sulfur bond length [44,45], and the different electron distribution of thioxopeptide bond ψ[CS-N] [46]. In the photostationary state, a fourfold enhanced myotropic activity was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Bond lengths and angles are listed in Table 2. Like other inhibitors of aldose reductase (Varma, Mikuni & Kinoshita, 1975;Kador, Sharpless & Goosey, 1982;Varughese, Przybylska, Sestani, Bellini & Humber, 1983), the sorbinil molecule contains a large planar aromatic region. The fragment of the molecule containing the phenyl ring and atoms O(1) and C(4) is essentially planar (largest deviation of an atom from the least-squares plane 0.02 A).…”
Section: Experimental Sample Of Sorbinil Provided By Pfizermentioning
confidence: 99%
“…Several structural changes upon going from amides to thioamides have been observed. The thioamide rotational barrier about the CSNH bond is approximately 8–12 kJ mol –1 larger than that for the amide (CONH) bond due to the more pronounced double bond character of the thiopeptide CN bond. , The longer CS double bond (1.64 Å) in comparison with the CO bond (1.24 Å), , as well as the larger covalent and van der Waals radii of sulfur, and modified hydrogen-bond-accepting abilities of thioamides affect the overall changes in the conformational behavior of thioamide-containing molecules. Some very recent studies have investigated the thioamide backbone in peptoids containing aromatic side chains. , These studies outlined earlier reported findings of the importance of n → π* interactions, characterized by the donation of electron density from the thiocarbonyl sulfur lone pair to the π* orbital of an adjacent amide carbonyl, in stabilization of the trans -amide conformation in a peptide chain .…”
Section: Introductionmentioning
confidence: 99%